Early Mobilization After Stroke: Do Clinical Practice Guidelines Support Clinicians' Decision-Making? - Rethnam, Venesha; Hayward, Kathryn S.; Bernhardt, Julie; Churilov, Leonid (Frontiers in Neurology, 2021)
Background: Early mobilisation, out-of-bed activity, is a component of acute stroke unit care; however, stroke patient heterogeneity requires complex decision-making. Clinically credible and applicable CPGs are needed to support and optimize the delivery of care. We aim to investigate the utility and limitations of early mobilisation CPGs to support clinical decision-making. Methods: Our study uses a novel, two-pronged approach. (1) a systematic review of CPGs containing recommendations for early mobilisation practices published after 2015 was appraised using purposely selected items from the Appraisal of Guidelines Research and Evaluation–Recommendations Excellence (AGREE-REX) tool relevant to decision-making for clinicians. (2) A cross-sectional study involving semi-structured interviews with expert stroke clinicians representing content experts and CPG target users. Every CPG was independently assessed against the AGREE-REX standard by two reviewers. Expert stroke clinicians, invited via email, were recruited between June 2019 to March 2020.The main outcomes from the systematic review was the proportion of criteria addressed for each AGREE-REX item by individual and all CPG(s). The main cross-sectional outcomes were the distributions of stroke clinicians’ responses about the utility of CPGs, specific areas of uncertainty in early mobilisation decision-making, and suggested parameters for inclusion in future early mobilisation CPGs. Results: In 18 identified CPGs, many did not adequately address the “Evidence” and “Applicability to Patients” AGREE-REX items. Out of 30 expert stroke clinicians (11 physicians [37%], 11 physiotherapists [37%], 8 nurses [26%]; median [IQR) years of experience, 14 [10-25]), 47% found current CPGs “too broad or vague”, while 40% rely on individual clinical judgement and interpretation of the evidence to select an evidence-based choice of action. The areas of uncertainty in decision-making revealed four key suggestions: (1) more granular descriptions of patient and stroke characteristics for appropriate tailoring of decisions, (2) clear statements about when clinical flexibility is appropriate, (3) detailed description of the intervention dose, and (4) physical assessment criteria including safety parameters. Conclusions: The lack of specificity, clinical applicability, and adaptability of current CPGs to effectively respond to the heterogeneous clinical stroke context has provided a clear direction for improvement.